Studies of Leading Catalysts for Olefin Metathesis: Evaluation of Synthetic Routes and Participation in Catalysis - Ou, Xinrui (Université d'Ottawa / University of Ottawa, 2021)
Olefin metathesis is increasingly popular for the construction of carbon-carbon double bonds. In the past two decades, ruthenium metathesis catalysts have seen extensive development. Two marvelous early developments were the introduction of N-heterocyclic carbene (NHC) ligands, which greatly improved catalyst activity, and replacement of a nucleophilic stabilizing ligand (the alkylphosphine PCy3) by a chelated benzylidene-ether. A more recent breakthrough is the introduction of cyclic alkyl amino carbene (CAAC) ligands as alternatives to the NHCs. Over the past 5 years, the CAAC catalysts have drawn much attention for their breakthrough productivity in challenging reactions, including ethenolysis and RCM macrocyclization. Nevertheless, important challenges remain. As discussed in the first part of this thesis, these include the synthesis of key ligands (in particular, the styrenyl ether ligands H2C=13CH-C6H4-2-OiPr and H2C=13CH-C6H3-2-OiPr-5-NO2), which represent the source of the chelated benzylidene-ether noted above) and key catalysts (e.g., Hoveyda- and Grela-class catalysts bearing an H2IMes or CAAC carbene ligand). A further challenge lies in understanding the behaviour of the styrenyl ether ligands – for example, how they contribute to catalyst partitioning between active, resting-state, and decomposed species, and the impact of the carbene ligand on that partitioning. An initial objective was synthesis of labelled styrenyl ethers that would enable synthesis of Hoveyda and Grela catalysts with a 13C-label at the alkylidene carbon. While H2C=13CH-C6H4-2-OiPr could be accessed, its nitro analogue could not, probably owing to attack on the NO2 substituent. The remainder of Chapter 2 assessed reported routes to HII/nG and HII-C1/nG-C1, and reports on challenges and reproducibility issues. Difficulties in synthesis of the CAAC catalysts are attributed to the need for in situ-generated CAACs, and catalyst decomposition by the base required for deprotonation (i.e KHMDS or LiHMDS). The second part of this thesis explores the impact of the NHC or CAAC ligands on initiation and “boomerang” recapture of the styrenyl ether ligands for Hoveyda- and Grela-class catalysts. Examination of the kinetics of initiation with bulky t-butyl vinyl ether (tBuVE) revealed a linear dependence of kobs on [tBuVE], and faster reaction by the p-NO2-substituted Grela catalyst. These data suggest an associative or interchange-associative (IA) mechanism. A systematic comparison of initiation rate constants revealed the trend HII > nG-C1 > HII-C1 in chlorinated and aromatic solvents. Recapture of added styrenyl ether ligand was examined in macrocyclization (mRCM). Rate plots indicated inhibition by this ligand, even at the high dilutions required for mRCM, implying that boomerang re-uptake of the styrenyl ether is indeed operative for both Hoveyda- and Grela-class catalysts. However, inhibition was found to be more profound for HII than HII-C1 or nG-C1. That is, the NHC catalysts are much more susceptible to partitioning into the off-cycle (precatalyst) form than are the CAAC catalysts. This higher commitment to the active cycle may be an important contributor to the impressive productivity of the CAAC catalysts. In addition, the slow initiation of these catalysts indicated above may be an asset, rather than a limitation, as it inhibits their susceptibility to bimolecular decomposition.
Keywords: Olefin metathesis